Advanced scheduling in data transmission and mobile media cloud computing - Yang, Ming (2015)
In general, scheduling can be considered as the way to efficiently arrange the usage of some shared resource (e.g. communications bandwidth and computing time) to complete multiple tasks or sub-tasks. In this thesis, three types of scheduling are investigated, including the data transmission scheduling in wireless MAC protocol, the CPU scheduling for media computing on mobile devices and the dynamic job scheduling in cloud system. In the data transmission scheduling, we study how to efficiently schedule a large amount of data transmission jobs in the resource constrained scenarios, particularly in the long-RTT (round-trip time) and low-bandwidth networks scenario. The MAC protocol of underwater networks is chosen as a study case to investigate how to overcome the limited resource. A new underwater MAC protocol is proposed where the design tackles the costly protocol handshakes by reducing the protocol handshake overhead and increasing the data transmission opportunities. An efficient dynamic polling-based handshake operation is designed which offers time-bounded collision-free channel assignment. Through extensive simulations, the results show the proposed HCFMA protocol outperforms its counterparts, in terms of throughput and delay, such as ALOHA with carrier sensing (ALOHA-CS) and slotted floor acquisition multiple access (SFAMA).